2012
DOI: 10.1158/1078-0432.ccr-12-0578
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab Induces Tumor Reduction and Bone Formation in Patients with Giant-Cell Tumor of Bone

Abstract: Purpose: Giant-cell tumor of bone (GCTB) is a locally aggressive, benign osteolytic tumor in which bone destruction is mediated by RANK ligand (RANKL). The RANKL inhibitor denosumab is being investigated for treatment of GCTB. We describe histologic analyses of GCTB tumor samples from a phase II study of denosumab in GCTB.Experimental Design: Adult patients with recurrent or unresectable GCTB received subcutaneous denosumab 120 mg every 4 weeks (with additional doses on days 8 and 15). The primary histologic e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
305
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(336 citation statements)
references
References 48 publications
17
305
1
13
Order By: Relevance
“…MRI check-up examinations showed that the previous cystic formations had been replaced with solid bone marrow-like tissue, a finding that has also been noted in GCT therapy [3]. Radiculopathy and neurologic symptoms also resolved in both patients.…”
Section: Discussionsupporting
confidence: 60%
“…MRI check-up examinations showed that the previous cystic formations had been replaced with solid bone marrow-like tissue, a finding that has also been noted in GCT therapy [3]. Radiculopathy and neurologic symptoms also resolved in both patients.…”
Section: Discussionsupporting
confidence: 60%
“…These observations match the known fact that XGEVA ® (denosumab) -a molecular targeted preparation composed of antiRANKL monoclonal antibodies -was in 2013 recommended by the American Food and Drug Administration for the treatment of inoperable GCBT [16,17]. It was shown that the clinical effect of denosumab observed in a considerable part of the patients was accompanied by more than 90% decrease of the number of tumor-associated giant cells and a decrease of the number of stromal cells [18]. RANK/RANKL interaction inhibitors are also considered as new approaches to the treatment of chordoma [19] and some benign bone lesions [10].…”
Section: Discussionsupporting
confidence: 78%
“…Single case reports indicated alterations in morphology such as benign fibrous histiocytoma-like (BFH) lesions [12]; fibrous cells with partial reactive bone formation; bone regeneration; aggregated inflammatory cells [13]; distinctive pseudosarcomatous spindle cell proliferation with matrix production and paucity of giant cells and mitosis; mimicking osteogenic sarcoma [14]; reactive stromal cells and scattered spindle cells with elongated oval-shaped nuclei without evident atypia and diffusely clustered foamy macrophages [15]; 5-10% necrosis with remaining GCT [16]; extensive necrosis and fibrosis without GCT [17]; lacking giant cells in the metastatic GCT to lung [18]. Branstetter et al evaluated GCTs' pre and posttreatment specimens by immunostaining with RANK, RANKL [19]. They demonstrated the osteoclastic arrest and presented histopathologic and immunohistochemical findings but they did not classify these changes.…”
Section: Discussionmentioning
confidence: 99%